Corrigendum to "EXAFS and DFT study of the cadmium and lead adsorption on modified silica nanoparticles" [Spectrochim. Acta Part A: Mol. Biomol. Spectrosc. 151 (2015) 156–163] - Arce, Valeria Beatriz (2015)
The authors regret to inform that in Fig. 7 of this article some information was missing. The corrected Fig. 7 is shown below.